Perancangan Sistem Monitoring Sun Tracker Dual Axis Berbasis Web Socket - Krisna Putra, I Wayan Eka; Sudarma, Made; Manuaba, Ida Bagus Gede (Majalah Ilmiah Teknologi Elektro, 2023)
Sun tracker is a system that developed to get the maximum energy of sun light while following the sun position. Most of the solar panels do not have this kind of technology to monitor the position that has the maximum voltage, thus a website application is made to monitor the voltage that is received by the sun tracker in realtime. Web socket technology is the solution to obtain information in real-time. Socket.io is the service that is used to fulfill this web socket technology in this development system. Socket.io is a web socket technology for websites that allows servers to process data in real time so that information on the angle position of the sun tracker and the voltage received by the solar panel can be sent to the website in real time. As a result, this monitoring system is able to move the solar panel in accordance with the direction of sunlight and display the angular position of the solar panel and graph of the voltage received by the solar panel directly (real-time) using socket.io. Keyword— Monitoring, Socket.io, Sun Tracker, Solar Panel